PENGEMBANGAN MATH ESCAPE ROOM BERBASIS UNPLUGGED CODING UNTUK MELATIH COMPUTATIONAL THINKING SISWA KELAS VIII MATERI PERSAMAAN GARIS LURUS - Dimas Teguh Nur Rohmad; Mohamad Aminudin (Universitas Islam Sultan Agung, 2026)
This research aims to develop a Math Escape Room based on Unplugged Coding (MER-UC) to train eighth-grade students' Computational Thinking (CT) skills in the Straight Line Equation (LLE) topic. The study used a Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation.The Analysis stage demonstrated that mathematics learning remains conventional and does not optimally train CT. The Design stage resulted in an escape room game design integrated with CT indicators: decomposition, pattern recognition, abstraction, and algorithmic thinking. The Development stage produced a product consisting of mission cards, instruction cards, worksheets, and teacher and student guides, validated by material and media experts. Implementation was carried out with eighth-grade students, while evaluation was conducted through quantitative and qualitative analysis.The results showed that MER-UC was categorized as adequate based on expert validation. Students' CT skills were in the good to excellent category. Qualitatively, students were able to identify important information, find patterns, simplify problems, and systematically organize problem-solving steps. Thus, MER-UC is declared feasible and potentially effective in training students' CT abilities. Keywords: Math Escape Room, Unplugged Coding, Computational Thinking, Straight Line Equations, ADDIE.